Charge transport in and electroluminescence from sp3-functionalized carbon nanotube networks - Zorn, Nicolas; Berger, Felix J.; Zaumseil, Jana (ACS nano, 2021)
The controlled covalent functionalization of semiconducting single-walled carbon nanotubes (SWCNTs) with luminescent sp3 defects leads to additional narrow and tunable photoluminescence features in the near-infrared and even enables single-photon emission at room temperature, thus strongly expanding their application potential. However, the successful integration of sp3-functionalized SWCNTs in optoelectronic devices with efficient defect state electroluminescence not only requires control over their emission properties but also a detailed understanding of the impact of functionalization on their electrical performance, especially in dense networks. Here, we demonstrate ambipolar, light-emitting field-effect transistors based on networks of pristine and functionalized polymer-sorted (6,5) SWCNTs. We investigate the influence of sp3 defects on charge transport by employing electroluminescence and (charge-modulated) photoluminescence spectroscopy combined with temperature-dependent current-voltage measurements. We find that sp3-functionalized SWCNTs actively participate in charge transport within the network as mobile carriers efficiently sample the sp3 defects, which act as shallow trap states. While both hole and electron mobilities decrease with increasing degree of functionalization, the transistors remain fully operational, showing electroluminescence from the defect states that can be tuned by the defect density.